(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article briefly compares the lexicographic, grammatical, and pragmatic features of formal speech in English and Uzbek. While formal speech in English tends to utilize neutral terminology, passive voice, and short, concise structures, the Uzbek language employs more fixed expressions based on respect and compliments, plural forms, and longer, polite expressions. These differences reflect the cultural values and norms of formal communication in both languages